Occurrence of Resistance to ALS Inhibitors in European Cyperus esculentus L.: Characterisation and Implications for Management - Laura Scarabel; Silvia Farinati; Maurizio Sattin (Agronomy, 2020)
Yellow nutsedge (C. esculentus) is a perennial geophyte and invasive weed which is very difficult to control in rice and other irrigated row crops. Acetolactate synthase (ALS) inhibitors are the most commonly used herbicides to control sedges in rice. Failure to control C. esculentus was recently reported in a rice field in north-western Italy. The resistance status of this C. esculentus population was determined through a whole-plant bioassay. The mechanism underlying the resistance was elucidated, and the available chemical and non-chemical control options were discussed. The population proved to be resistant to halosulfuron and azimsulfuron at the recommended field rate. The ALS trancripts amplified from resistant and susceptible plants revealed the presence of a Pro197-to-Arg amino acid substitution in resistant plants, indicating that the resistance mechanism is target-site mediated. This is the first confirmation of herbicide resistance in C. esculentus in Europe. Resistance management should be based on an integrated approach, through the combination of diversified cultural and agronomic practices that can limit its spread and propagation through tubers.